The debate on staff language competences and the use of official languages in the Balearic Islands health system - Ballester Cardell, Maria; Marí Mayans, Isidor (Linguistic Minorities and Society, 2021)
The Spanish Constitution of 1978 and the Statute of Autonomy of the Balearic Islands of 1983 established the official nature of both Spanish and Catalan and entrusted public authorities with guaranteeing the right of citizens to use one or the other on an equal footing. Subsequent to the language legislation of 1986, the legal framework of Catalan has varied depending on the majority party that forms a government. The debate stirred up by these regulations demonstrates the difficulties in ensuring real equality between official languages, when social initiatives cannot translate into sufficient political support and the national political context is hostile. The article explores this debate and discusses recent regulations surrounding the official languages competencies of health system staff, from the direct experience of the authors, as members of two consultative institutions on legal and sociolinguistic matters. Keywords: language rights, official language, language competence, medical communication, health services

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

The language barrier : the overlooked challenge to equitable health care - Hussey, Nadia (South African Health Review, 2012)
This chapter examines the effects of language barriers on the access of patients and communities to quality health care. It also looks at communication challenges experienced by health professionals that provide this care. Using a case study of a rural hospital, the chapter highlights some of the challenges posed by the language barrier and explores current methods that English-speaking health professionals at this hospital use to overcome these difficulties. The case study findings indicate that the language barrier decreases work efficiency and the provision of holistic treatment. It makes communication time consuming, which increases frustration levels and decreases empathy, approachability and confidentiality. Current methods for overcoming problems include the use of untrained and ineffective interpreters - usually overworked nurses; linguistic codeswitching; and the use of a selection of key isiXhosa vocabulary. These methods have many drawbacks and are not suitable or sustainable. Recommendations for improving communication include the promotion of a culture of multilingualism, which includes language education as a part of professional development and the employment of trained interpreters. For multilingualism to occur, more research needs to be conducted, and the political will to address this problem must be demonstrated. Overcoming the language barrier needs to be prioritised and commitment must be made to implementing strategies that provide a multilingual patient base with a multilingual healthcare service.

Bilingualism in the health system: The Catalan case - Ibáñez Ferreté, Òscar-Adrià; Mestres i Farré, Neus (Linguistic Minorities and Society, 2021)
Catalan-speaking citizens living in Catalonia have full, formal rights to use their language with all of their region’s administrations. Nevertheless, the available information on the knowledge and use of Catalan by civil servants shows that health care is a weak spot for regional administrations, due to the difficulty in covering all medical specialties. Plataforma per la Llengua has undertaken research in the form of a survey with a sample of 1,600 Catalan inhabitants, to ascertain the level of satisfaction with the enforcement of linguistic rights in public health and determine the scope of a potential language promotion policy that would have health care staff initiate conversations in Catalan. Results of government surveys suggest that language use (by both patients and providers) in the health care system, compared with language use in other areas of public administration, demonstrates the limits of the current regional language promotion policies in Catalonia. Keywords: catalan, linguistic minorities, linguistic rights, health and social services, language competencies

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.

The Basque paradigm shift: From legislative language policies to person-centred care - Montes Lasarte, Aitor; Arauzo, Xabier; Zarate Sesma, Jon (Linguistic Minorities and Society, 2021)
The Basque Country has two official languages, Basque and Spanish, the first being spoken by 37% of the population. The Basque Health Service has developed language schemes to fulfill the legal requirements. Currently, there is a vast transformational shift from legislative policies to an evidence-based, patient-centred care approach. This paper discusses three key issues which could enhance language appropriate care: the recording of patient’s preferred language; the Basque language care pathways as a suitable and effective approach for determining the language of service along the continuum of care; and bilingual electronic medical records, which bring to the fore the challenge of language barriers among professionals. Considering its bilingual human resources, it offers an opportunity for establishing compelling evidence about implementation. Keywords: patient-centred care, bilingual pathways, language appropriate care, preferred language, active offer

Approach to the status and management of languages in the catalan public health care system - Pere Mas, Jordi (Linguistic Minorities and Society, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health. Keywords: healthcare, health, Catalan, linguistic planning, healthcare professionals, official languages, Catalonia

Therapists’ views on working with bilingual Spanish-English clients: A qualitative inverstigation - Santiago-Rivera, Azara. L.; Altarriba, Jeanette; Poll, Norma; Gonzalez-Miller, Normaris; Cragun, Cragun (Professional Psychology: Research and Practice, 2009)
Through semistructured interviews, language switching in therapy was examined with 9 bilingual Spanish and English therapists. Therapists were asked about how and when they switched from one language to another during treatment, as well as the ways in which their clients’ switched languages. After the use of consensual qualitative research methods (C. E. Hill et al., 2005; C. E. Hill, B. J. Thompson, & E. N. Williams, 1997), the results revealed that therapists used language switching as a mechanism to establish trust, bond with clients, and promote disclosure through the use of specific phrases or specific words; particularly, the use of Spanish idiomatic expressions (dichos) served to engage, redirect, and increase client self-understanding and awareness. Therapists reported that their clients switched from English to Spanish when recounting experiences that involved certain emotions (e.g., anger) and represented themselves differently depending on the language they were speaking. Therapists also reported that their clients switched from English to Spanish to improve communication and to connect with them. Future directions for research and implications for training and practice are outlined. (PsycInfo Database Record (c) 2025 APA, all rights reserved)

La santé et les minorités linguistiques : l’approche canadienne au regard de cas internationaux - Traisnel, Christophe; Forgues, Éric (Francophonies d'Amérique, 2009)
Dans notre article, nous présentons une analyse comparative de l’approche canadienne de l’enjeu de la santé pour les communautés francophones en situation minoritaire (CFSM). Nous montrons que l’État canadien a favorisé une démarche de concertation avec les acteurs communautaires. Notre analyse comparative nous a permis de dégager une typologie des politiques linguistiques en matière de santé destinées aux CFSM. Cette typologie permet de situer l’expérience canadienne par rapport à d’autres expériences, parfois proches, mais présentant des perspectives différentes, comme le montrent les cas finlandais, belge et états-unien. La « voie » canadienne paraît originale dans la mesure où elle semble se situer entre un modèle communautaire, à l’instar des pays européens, et un modèle individualisé, à l’instar de ce qui se fait aux États-Unis.